Association Of TNF-Α With Obesity In Type 2 Diabetes Mellitus - D.RAJARAJESWARI; K.RAMALINGAM; M.KRISHNAMMA; T.SHARMILA KRISHNA (International Journal of Pharma and Bio Sciences, 2011)
Recent work in the area of Obesity has confirmed that Obesity is a state of low grade chronic inflammation and is associated with increased levels of TumorNecrosisFactor-α, a pro-inflammatory adipocytokine, which plays a key role in the pathogenesis of Diabetes. In this study we analysed the interrelations between TumorNecrosisFactor-α with anthropometric and clinical variables. The study was carried out on a total of 100 subjects attending outpatient department of General Medicine, Narayana Medical College, Nellore. Serum TumorNecrosisFactor-α was measured by sandwich ELISA method and insulin by chemiluminescence method. TumorNecrosisFactor-α was significantly elevated in diabetic cases[215.18+ 119.58] compared to controls[p= 0.0001]. There was significant positive correlation between TumorNecrosisFactor-α and Body Mass Index. TNF alpha levels were significantly elevated in obese than in non-obese diabetic subjects. Our results suggest a possible role of TNF-alpha in the pathophysiology of Type2 Diabetes mellitus.